EXPERT SYSTEM REKOMENDASI PERJALANAN WISATA DANAU TOBA MONACO OF ASIA - Sahat Sonang; Erwin Sirait (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Tourism is becoming one of the world's largest industries year after year. Tourism has a lot of positive effects on the region, such as increased tax revenue, job creation, foreign exchange earnings, and development spread. Traveling is still a popular activity, which has led to new ideas and confusion among travelers about where to go. This is the issue with urgency. The fact that a lot of websites designed for informational purposes and travel booking on the internet are still regarded as basic and static, even though they were made by public and private organizations, is another issue. It is believed that the website provider gives user response and interaction scant consideration. The recommendation of tourist attractions that are appropriate for tourists is the goal of this study. The public's direct recommendations for cultural tourism are mapped out in this tourism recommendation system along with general and cultural tourist attractions. This tourism recommendation system uses genetic algorithms to suggest both cultural and general tourist destinations. Criteria about tourist destinations or places you do not want to visit, as well as priority places or tourism types you want to visit, will be added to this research. The genetic algorithm processes these criteria, and based on the criteria, has been able to generate travel recommendation results that are more optimal and accurate.